Implementation of The VAK-Based QuizWhizzer Game: A Case Study At SDN Naru Ranggasolo Bima - Angriani, Runy; Irawan, Ady; Haryadi, Didit (FKIP - Universitas Riau, 2025)
The objectives of this research are: (1) To examine the influence of using a VAK model-based QuizWhizzer game on the Civics cognitive PPKn (2) To determine the effectiveness of the VAK model-based QuizWhizzer game in improving the Civics cognitive PPKn, and (3) To identify the factors that influence the Civics cognitive PPKn. This research uses a quantitative approach with a pre-experimental method and a One Group Pretest-Posttest design. The research was conducted in Class V of SDN Naru Ranggasolo.The data collection techniques used in this research include test and non-test methods. The test instrument consisted of pretest and posttest questions. The non-test instrument was in the form of documentation. The results of the research showed a significant increase in the average score, from 57.50% in the pretest to 85.83% in the posttest. The paired sample t-test results showed a significance value of 0.000 (p < 0.05), which confirms a significant influence of using the VAK model-based QuizWhizzer game on the Civics cognitive abilities of students. Therefore, the use of interactive games has proven to be influential and effective and is one of the factors supporting the improvement of these abilities.